Letter to America - Trifonova, Iglika, 1957-; Avramov, Filip; Klas film (Firm); Eastwest Film Distribution GwBH (Sofia : KLAS film ; Amsterdam : Phanta Vision International ; Budapest : Budapest Filmstudio, 2001)
Ivan's best friend, Kamen, is dying in an American hospital. Since he's denied a visa to the USA and can't stay by his side in his last moments, he decides to set off for Bulgaria countryside, taking the camera Kamen has given him. After some time, he writes her a very special letter, telling all about the places and characters he meets on his way, witnesses to a time which is bound to be forgotten. --
Originally released as a motion picture in 2001.
European co-production supported by Eurimages, The Bulgarian National Film Centre, The Motion Picture Public Foundation of Hungary-MMKA, ZDF/Arte in co-production with Boyana Film Company, the Bulgarian National Television.
Philip Avramov, Ana Papadopulu, Peter Antonov.
Cinematographer, Raly Ralchev; editors, Jordanka Bachvarova, Floor Smal; music, Milcho Leviev.
Bulgarian with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 9, 2015).
Keywords: Friendship -- Drama; Road films; Feature films; Internet videos; Streaming video